Assessing the Impacts of Shamba Shape Up: A report commissioned by AECF and led by University of Reading - Africa Enterprise Challenge Fund (2015)
1. AECF commissioned a study to investigate the impact of the Shamba Shape Up TV edutainment programme on small-scale agriculture in Kenya and to research the processes by which the programme influences farmers’ activities 2. The assessment is based on a theory of change that draws on three bodies of theory and research which have informed the design of the Shamba Shape Up initiative: mass media and society; agricultural and rural extension; and innovation systems 3. The study focused on the area of Kenya that Shamba Shape Up is targeted at and the rigorous statistical design of the assessment allows robust estimates of the size of the audience, and of the effects of Shamba Shape Up at farm and population levels 4. Two questionnaire surveys were conducted across 119 Enumeration Areas together with a more detailed study at selected locations using participatory tools 5. In the 26 rural and peri-urban counties which comprise the main target audience, Shamba Shape Up is viewed in 12.6% of sampled households 6. Most viewers report that the programme has helped them improve the profitability of their enterprises and has had a positive effect on their families’ food situation 7. Shamba Shape Up covers a range of enterprises. This assessment focussed mainly on maize and dairy as they were the most focused on. In both enterprises, viewers of the programme were significantly more likely to have made changes in practice featured in broadcasts, and to have made more changes, than non-viewers, even when other socio-economic variables are taken into account 8. The overall number of households specifically reporting that they had made changes to their maize or dairy practices as a result of the programme, or who reported that they had benefited from SSU through increased profit or improved household food situation, is statistically estimated to be 428,566 9. Households who reported making specific changes in their farming practices as a result of Shamba Shape Up are statistically estimated to be 218,562 households for maize and 65,063 for dairy 10. From these two enterprises, the statistically estimated net economic impact in the 25 counties was US$24,718,648; this comes mostly from dairy enterprises. 11. Viewers reported a range of effects of the programme, beyond the impact on output and profitability: these included improved food security and nutrition, confidence in their management ability, enhanced social status and the re-investment of increased income in other, off-farm, livelihood activities 12. Findings from detailed participatory budgets indicated that gross margins for maize and dairy have improved for viewers of the programme over the past two years, and to a greater extent than for non-viewer SHAMBA SHAPE UP 2014 PAGE 5 SSU: List of Tables 13. There is some evidence that women dairy farmers who have made changes influenced by the programme have been able to reduce the gap in gross margins between them and male dairy farmers 14. Trust in a source of information and influence has a significant effect on the likelihood that farmers will make changes promoted or suggested by the source; Shamba Shape Up scores higher on trust than other more conventional sources of information among viewers of the programme 15. Most viewers identify with the problems farmers face in the broadcasts, care about the families shown and feel involved with them 16. Most viewers feel that they get useful information from the programme and that it helps them make decisions on their own farms; they learn things that they can try out; and they also find the broadcasts enjoyable to watch 17. The programme has become an important part of farmers’ information and innovation systems, operating as a trusted source of information presented in a format that engages their interest and emotions, encourages discussion and provides opportunity for follow-up and interaction